KELANGSUNGAN HIDUP, PERTUMBUHAN DAN TINGKAT KONSUMSI OKSIGEN IKAN PATIN (Pangasius sp.) YANG TERPAPAR LIMBAH CAIR PABRIK KELAPA SAWIT - Resti Amalia; Marsi .; Ferdinand Hukama Taqwa (Universitas Sriwijaya, 2013)
The current research aimed to know the lethal and sub-lethal toxicities of industrial palm oil liquid waste on catfish. The reseach was carried out from May to June 2013 at Basic Fishery Laboratory, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University, Indralaya. This research used a Completely Randomized Design (CRD) with 7 treatment levels and three replications. At lethal experiment, treatment levels tested were without the addition of liquid waste (A), 13.18 mL.L-1 (B), 13.89 mL.L-1 (C), 14.63 mL.L-1 (D), 15.4 mL.L-1 (E), 16.21 mL.L-1 (F), and 17.06 mL.L-1 (G). For sub-lethal, treatment levels tested were without the addition of liquid waste (A), 0.5% x 96-h LC50 (B), 1% x 96-h LC50 (C), 6.25% x 96-h LC50 (D), 12.5% x 96-h LC50 (E), 25% x 96-h LC50 (F), and 50% x 96-h LC50 (G). The result of probit analysis shows 96-h LC50 value is 14.12 mL.L-1, positive linier relationship between mortality and concentration of palm oil liquid waste was found (r = 0.98 **). For the result of sub lethal concentrations of palm oil liquid waste ≤ 1% x 96-h LC50 had no effect (p> 0.01) while concentration of ≥ 6.25% x 96-h LC50 had very significant effect on the survival, growth and oxygen consumption rate of catfish. Key words : Toxicity, Industrial Palm Oil Liquid Waste, Catfish, 96-h LC50